THE USE OF GOOGLE SITES IN TEACHING DESCRIPTIVE TEXT IN EFL CLASSROOM - Nur Aulia; Ryan Rayhana Sofyan; Muhammad Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study is to find out the effectiveness of using Google Sites in learning English, especially on students’ ability to write descriptive text. The method in this study was quasi-experimental design by describing the data obtained through writing test and questionnaire. The population of this study was 50 students consisting of two classes. Class X TSM (Teknik Sepeda Motor) as the experimental class which consist of 25 students and X TKR (Teknik Kendaraan Ringan) as the control class which consist of 25 students. Then, the findings of this study indicated that there was a significant influence towards students’ ability to write descriptive text after utilizing Google Sites. It was attested by the students’ mean score from post-test was higher than in pre-test. The students’ mean score in pre-test at experimental class was 70.20 and in post-test was 90.80. Meanwhile, in control class, the students obtained the mean score in pre-test was 66.96 and in post-test was 88.40. Apart from that, the result of t-test was counted by applying IBM SPSS version 29, it can be viewed at the significant value was 0.000. Further, it was lower than 0.05 (0.000<0.05). It can be interpreted that the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. It can be concluded that there was a significant distinct outcome between utilizing and without utilizing Google Sites towards students’ ability to write descriptive text.